MICROFINANCE BANKS OPERATIONS AND ECONOMIC DEVELOPMENT IN NIGERIA - Omorose A. Ogiemudia; Igbinovia Lawson Eghosa; Amenze S. Airhiavbere (Oradea Journal of Business and Economics, 2022)
The paper explored the influence of Microfinance Banks (MBs) on Economic Development (ED) in Nigeria. It was embarked upon against the background that as statutory function, loans should be provided by MBs to spur developmental purposes that will improve long run living standard. Microfinance annual data stream sourced from the country’s Central Bank of Nigeria (CBN) statistical report and World Bank national accounts data spanning 1992 to 2020 were analysed with Autoregressive Distributed Lag (ARDL) ECM Model. Following detailed time series estimation, findings reveal that MBs, investment, assets, savings and aggregate credit (loans) significantly influence Nigerian ED during the studied period. Thus, this study concludes that MBs operations in Nigeria is a salient financial inclusion catalyst that significantly spur economic development in Nigeria during the sample studied.